Odpowiedzi

2010-04-11T21:45:12+02:00
A)
x+3y-12=0
2x-y-3=0

x+3y=12
2x-y=3

x=12-3y
2(12-3y)-y=3
24-6y-y=3
-7y=-21
y=3

x=12-3*3
x=12-9
x=3

spr:
x+3y-12=0
3+3*3-12=0
3+9-12=0
0=0



b)
2x-y-5=0
3x=y-6

2x-y=5
3x-y=-6

-y=5-2x
3x-y=-6

y=-5+2x
3x-(-5+2x)=-6
3x+5-2x=-6
x=-11

y=-5+2*(-11)
y=-5-22
y=-27

spr:
2x-y-5=0
2*(-11)-(-27)-5=0
-22+27-5=0
0=0



c)
x+4y-14=0
3x-y=20

x+4y=14
3x-y=20

x=14-4y
3(14-4y)-y=20
42-12y-y=20
-13y=-22
y=1⁹/₁₃

x=14-4*1⁹/₁₃
x=14-6¹⁰/₁₃
x=7³/₁₃

spr:
x+4y-14=0
7³/₁₃+4*1⁹/₁₃-14=0
7³/₁₃+6¹⁰/₁₃-14=0
0=0